Edukasi Perlindungan Hak Merek Sebagai Strategi Pemasaran Produk PT. Cisarua Mountain Dairy (Cimory) - Dewi Lestari, Ni Ketut Sucia; Antari, Putu Eva Ditayani (Nawadeepa: Jurnal Pengabdian Masyarakat, 2024)
PT. Cisarua Mountain Dairy (Cimory), a producer of premium food and dairy products in Indonesia, was established in 2005. This article emphasizes the importance of brand protection education as a marketing strategy for Cimory. This protection is regulated by Law No. 20 of 2016 concerning Trademarks and Geographical Indications, which covers registration, exclusive rights, and law enforcement. Trademark registration provides exclusive rights and prevents unauthorized use. The research method involved a direct visit to Cimory Dairy Land On The Valley in Semarang, where the author gathered information about brand identification, production processes, and trademark protection. The research results indicate that brand protection education is crucial for maintaining brand reputation and integrity, as well as reducing the risk of infringement. Companies like Cimory can be more effective in protecting their intellectual assets, preventing unauthorized use, and maintaining consumer trust. Steps such as trademark registration and internal education are key to marketing strategies aimed at strengthening brand positioning in the market and preventing potential infringements that could harm the company.